Assessment of the relationship between stress and temporomandibular joint disorder in female students before university entrance exam (Konkour exam) - Ahmad Mottaghi; S Mohammad Razavi; Elham Zamani Pozveh; Milad Jahangirmoghaddam (Wolters Kluwer Medknow Publications, 2011)
Background: Temporomandibular joint is one of the most complicated joints of the body and plays an important role in the head and neck system. One of the factors affecting the temporomandibular joint and lead to temporomandibular disorder is anxiety with all the events causing it. The aim of this study was to determine a relationship between anxiety and temporomandibular disorders. Materials and Methods: In this prospective study, subjects were randomly selected. One hundred and thirty pre-university students in Isfahan were evaluated with Ketel's test of anxiety, exam stress test and temporomandibular disorder questionnaires. The evaluation was done in two stages 10 months and 1 month prior to the university entrance exam (Konkour), clinical assessments consisted of masticatory muscles and sternocleidomastoid muscle palpation, temporomandibular joint palpation for pain and noise and its movement, and mouth opening limitations. The Wilcoxon rank test and paired t-test were used to analyze the data and the P value under 0.05 was considered significant. Results: The level of anxiety and occurrence of temporomandibular disorders were increased between two stages and had the highest level in the second stage. There was a significant increase between two stages (P<0.001). Conclusion: The parallel increase of temporomandibular disorders and anxiety between the two stages can suggest a possible relationship between anxiety and temporomandibular disorders. Therefore, the effect of anxiety in triggering temporomandibular disorder symptoms is probable.